Facebook: Can it be a Tool to Transform Pedagogical Practice in Higher Education amongst Asian Generation Y Students?: Challenging Expectations - LUTHRA, Poornima (Institutional Knowledge at Singapore Management University, 2014)
Facebook is increasingly making its way into tertiary classrooms with instructors tapping into new technology to transform their pedagogy to better engage with students. However, the use of Facebook in higher level education in Asia is a fairly new phenomenon. This paper presents the findings from a study on the use of Facebook as a forum for classroom discussion in a tertiary institution with majority Asian students. The instructor set up closed Facebook groups that were used to share articles and videos, and post comments with the objective of expanding the interaction amongst students, and between students and the instructor. While prior research seems to indicate that Generation Y students would appreciate the use of a technological medium that they are comfortable with in education, the results suggest otherwise. Firstly, students view Facebook as being a part of their personal sphere and by using it for educational purposes, it’s viewed as an invasion into their personal space. Students view Facebook as an informal medium and a place to relax and socialize with their chosen friends, not to “work”. Secondly, the majority Asian Generation Y students that were studied seemed to be very conscious about their self-image on Facebook. They worried about how their peers would view them should their posts not generate discussion. This can be attributed to the Asian value of protecting one’s image or “face”. Lastly, while students agree on the merits of Facebook, they do not see it as an effective study tool, particularly to generate discussion.